Promoting Climate-Resilient Agrifood Systems Governance with Gender Inclusivity: A Policy Brief - Amoak, Daniel; Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2023)
Although livelihoods within agrifood systems (AFS) are generally vulnerable to the impacts of climate change, women bear a disproportionate burden from rising climatic stressors. In agrarian regions in the Global South, women face unique and intersectional vulnerabilities that limit their voice in governance and decision-making processes. This, in turn, impedes their ability to participate in and benefit from the food system. Addressing these vulnerabilities is crucial for promoting women's empowerment, enhancing climate resilience, and ensuring food security at various levels, with a particular focus on community-level participation in AFS. This policy brief highlights existing evidence on barriers women face in agri-food system (AFS) governance and known approaches that can be scaled up to improve women’s voice and agency in climate relevant AFS governance.